PENGARUH PENGETAHUAN, KEPEDULIAN DAN SIKAP PADA LINGKUNGAN TERHADAP MINAT PEMBELIAN PRODUK HIJAU - Ristianawati Dwi Utami; Tri Gunarsih; Triana Aryanti (Trunojoyo University of Madura, 2014)
The main issues of this study is how cognitive and affective factors influencegreen products purchase. The objectives of this study are: (1) examine the influence ofenvironmental knowledge on green purchase intention based on gender differences as amoderating variable, (2) examine the influence of environmental concerns on on greenpurchase intention based on gender differences as a moderating variable, (3) examinethe influence of attitude on green purchase intention based on gender differences as amoderating variable, (4) examine the influence of gender on green purchase intentions.Results of this study are (1) environmental knowledge does not significantly influencegreen purchasing intention when moderated by gender with pvalue (0.560) 0.05, (2)environmental concern does not significantly influence green purchase intentions whenmoderated by gender with pvalue (0.475) 0.05, (3) green purchase attitude are notsignificantly influence green purchase intentions when moderated by gender with pvalue(0.781) 0.05, (4) gender diferences are not influence green purchase behavior withpvalue (0.628) 0.05. These results contrast with previous findings Tikka (2000) whoexplains that men are more likely to have more envormental knowledge compared withwoman. The findings also do not support research cby Mohai (1992) and Stern (1992)who found that women are more concerned about the environment than men andMustafa (2007) which states that women express greater environmental concern thanmen . But research is supported by the findings of Chen and Chai (2010) that there is nodifference between the attitude of male students and female students on the environmentand green products.